Can titanium elastic nail be safely used for paediatric subtrochanteric femur fractures?. Issue 1 (January 2021) - Basa, Can Doruk; Kacmaz, Ismail Eralp; Zhamilov, Vadym; Reisoglu, Ali; Agus, Haluk
Abstract : In this study, we aimed to show that subtrochanteric femur fractures, an uncommon type of fracture in the paediatric age group, can be treated with titanium elastic nailing (TEN). We reviewed the patients treated with TEN in the paediatric age group with subtrochanteric femur fractures who had been treated at the Orthopaedics and Traumatology Clinic of Izmir Tepecik Research and Training Hospital between January 2011 and December 2016 retrospectively. All fractures were fixed by retrograde nailing with supracondylar entry following reduction. Patients' demographics as well as data such as fracture type, fracture level, time of operation, reduction type, time to union, shortness, additional fixation, duration of additional fixation, Flynn scores and reduction loss were evaluated. The 20 patients included in our study were followed up for at least 1 year, had an age range of 54–173 months (mean, 104 ± 31.82 months) and were operated within 2–11 days after fracture. All patients had fracture union and only three patients had union with an angulation of less than 5°. None of the patients had limb length inequality. Fourteen patients underwent reoperation, all of these were routine operations for implant removal and no patients required reoperation for complications. We think that paediatric subtrochanteric femur fractures can be treated by TEN fixation using the proper technique, with a limited invasive intervention.